Pengaruh Penerapan Sistem Informasi Akuntansi, Sistem Pengendalian Internal, dan Kompetensi Sumber Daya Manuasia Terhadap Kualitas Laporan Keuangan dengan Good Governance Sebagai Variabel Pemoderasi - Norma Riza Umami Sarwono; Munari Munari (Universitas Batanghari, 2022)
This study aims to test and analyze the influence of the application of accounting information systems, internal control systems, and human resource competencies on the quality of financial statements with good governance as a coding variable. The type of research in this study is quantitative. The population used in this study was 60 employees at the Regional Office of the Ministry of Religious Affairs of East Java Province who were involved in financial management. The sampling technique uses a simple random sampling method. Based on the criteria or considerations that have been set, 52 respondents were obtained as a research sample. All tests in this study used the help of the SmartPLS 3.0 software analysis tool to test the relationship between the variables in it. The subject of the study or what is often referred to as the respondents used in this study is the staff of the finance department who are actively involved in the budget preparation team who are responsible for the results of the achievement of budget realization at the Regional Office of the Ministry of Religious Affairs of East Java Province. The results of this study show that the accounting information system has a positive and significant effect on the quality of financial statements, the internal control system has a positive and significant effect on the quality of financial statements, the competence of human resources has a positive and significant effect on the quality of financial statements, good governance does not moderate the relationship between the information system and the quality of reports, good governance does not moderate the hub of the internal control system to the quality of financial statements. Good governance moderates the relationship between human resource competence and the quality of financial statements.